5(2x-7)-3(x+2)-17x=

Simple and best practice solution for 5(2x-7)-3(x+2)-17x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-7)-3(x+2)-17x= equation:


Simplifying
5(2x + -7) + -3(x + 2) + -17x = 0

Reorder the terms:
5(-7 + 2x) + -3(x + 2) + -17x = 0
(-7 * 5 + 2x * 5) + -3(x + 2) + -17x = 0
(-35 + 10x) + -3(x + 2) + -17x = 0

Reorder the terms:
-35 + 10x + -3(2 + x) + -17x = 0
-35 + 10x + (2 * -3 + x * -3) + -17x = 0
-35 + 10x + (-6 + -3x) + -17x = 0

Reorder the terms:
-35 + -6 + 10x + -3x + -17x = 0

Combine like terms: -35 + -6 = -41
-41 + 10x + -3x + -17x = 0

Combine like terms: 10x + -3x = 7x
-41 + 7x + -17x = 0

Combine like terms: 7x + -17x = -10x
-41 + -10x = 0

Solving
-41 + -10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '41' to each side of the equation.
-41 + 41 + -10x = 0 + 41

Combine like terms: -41 + 41 = 0
0 + -10x = 0 + 41
-10x = 0 + 41

Combine like terms: 0 + 41 = 41
-10x = 41

Divide each side by '-10'.
x = -4.1

Simplifying
x = -4.1

See similar equations:

| 9(x+4)=6(2x+4) | | 2x+y=3y+20 | | A(y-v)=x | | 1/8x-1/9x= | | 6-2(7-x)=56 | | 4(2x+3)=6(2-1) | | 5x^4-4x^5=.5 | | -15x+3=-2x+3 | | 8(x+w)=a | | 4x-3/6=3x-2 | | -7x-5=-75 | | 4(x+2)-2=10 | | 2(6+x)+2=2(4x-x)+2 | | 5(x-4)-3(x-2)=5x-15 | | Y*2-7*w=3x | | 5/8*n=72 | | 5tan(2x)=4 | | 3x+45=9x-5 | | K-6K=22 | | 7/9x79/9 | | 4x+5=-10x+1 | | 2y/5=3y-4 | | y=5/8x-7/2 | | 5x+3-2x+1=12 | | 5*(x+1)+1=36-(5-x) | | 1/3.3/4=3/8 | | 8n(n-5)forn=5 | | 12n=9/14 | | 40/x=2.1x/21 | | 476=68t | | -7y+14=4y-2 | | 2(5x+8)=3(2x+4) |

Equations solver categories